The intertextuality of Shakespeare´s "King Lear" in relation to "The True Chronicle History of King Leir" and Spencer´s "Faerie Queene" - Staňková, Jindřiška (Univerzita Pardubice, 2007)
This bachelor paper deals with the accusation of plagiarism concerning Shakespeare's King Lear in recent history, resulting from changes that the understanding of ownership of ideas has undergone. The matter is very complex and therefore, in the first part of this paper the concepts of intertextuality, Romantic notion of author and authorship are discussed. The following part examines the most serious critique Shakespeare has been subjected to by Leo Tolstoy, and continues centering on the possible sources Shakespeare may have used, along with some terminology concerning the editions of King Lear and the dates of publishing. Finally, after examining Spencer's Faerie Queene and the supposed primary source, King Leir on their own, the paper reaches the point where King Leir and King Lear are compared.
Intertextualita Shakespearova "Krále Leara" ve vztahu k "Pravdivé kronice o králi Leirovi" a Spencerově "Královně víl"
Keywords: King Lear; King Leir; Plagiarism; intertextuality; William Shakespeare; Král Lear; Král Leir; Plagiátorství; intertextualita